OPTIMIZING PUBLIC PROCUREMENT IN BUDGET ORGANIZATIONS: INSIGHTS FROM UZBEKISTAN’S LEGAL FRAMEWORK AND INTERNATIONAL BEST PRACTICES - Turabov Sarvar Abdumalikovich (European Science Publishing, 2024)
This study examines Uzbekistan’s public procurement framework, focusing on budget organizations and the roles of regulatory bodies in ensuring transparency, accountability, and compliance. Key legislative documents, including the Law on Public Procurement and Resolution No. 3953 of the Cabinet of Ministers, provide the foundation for procurement practices that support socio-economic objectives, foster local industries, and improve public service delivery. The study employs a qualitative approach to analyze legislative documents and international standards, comparing Uzbekistan’s practices with those of OECD countries and World Bank recommendations. Findings reveal that while Uzbekistan’s procurement system aligns well with global standards, areas for improvement remain, particularly in digital infrastructure and procedural efficiency. By addressing these challenges, Uzbekistan can enhance the effectiveness of its procurement processes, contributing to sustainable economic growth and improved governance.
Keywords: Public procurement, budget organizations, transparency, Uzbekistan, regulatory bodies, digital procurement, socio-economic impact, international standards, compliance, Anti-Monopoly Committee.